MYELODYSPLASTIC SYNDROME AND GRAVES’ DISEASE - Ng, Yong Siang; Goh, Qing Ci; Mak, Woh Wei; Krishnan, Gayathri Devi; Ng, Yoke Mui; Redzuan, Shazatul Reza Mohd; Rajoo, Subashini; Bidin, Mohamed Badrulnizam Long (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Myelodysplastic syndrome (MDS) is a heterogeneous group of hematopoietic neoplasms characterized by bone marrow failure resulting in cytopenia and dysplastic haematopoiesis. The association between MDS and autoimmune diseases has been previously described in the literature. Here we report a case of Graves’ disease (GD) with secondary MDS. CASE A 43-year-old male with vitiligo was admitted for pancytopenia and left parapneumonic effusion. GD was concomitantly diagnosed based on weight loss, tachycardia, exophthalmos and the presence of TSH receptor antibodies. Antithyroid drugs were carefully used with close monitoring of cell counts. Despite clinical improvement with antibiotics and achievement of biochemical control of hyperthyroidism, cytopenia persisted. Results showed WBC 1.58 to 3.38 x 109/L, absolute neutrophil counts 0.65 to 1.18 x 109/L, haemoglobin 9.6 to 10.6 g/L, and platelet counts 74 to 107 x 109/L. Autoimmune panels tested negative. Peripheral blood film revealed pancytopenia without evidence of haemolysis or blast cells. Bone marrow aspirate and trephine biopsy showed mildly hypocellular marrow with relatively reduced myelopoiesis together with subtle dysplastic changes of erythrocytes and megakaryocytes. No cytogenetic abnormality was detected. Emerging evidence suggests that autoimmune diseases are risk factors for MDS. A Swedish population-based study demonstrated an apparent link between the development of MDS and autoimmune diseases. Most of the reported cases had a history of hypothyroidism. The development of MDS in relation to autoimmune diseases is still poorly understood. The proposed explanations include shared genetic or environmental risk factors, a direct insult to the bone marrow leading to malignant transformation by untreated autoimmune diseases, or the inflammatory process from a haematological neoplasm resulting in the subsequent diagnosis of an autoimmune disease. CONCLUSION Our case highlighted the association between autoimmune thyroid disease (GD) and MDS. Further studies to underpin the association and pathophysiology are required.